Proyecto de factibilidad para la creación de una empresa de reciclaje de cartuchos de tinta y toners en la ciudad de Guayaquil - Celi, Alejandro (2010)
The project is based on the creation of a recycling company ink and toner cartridges (printer supplies) in the city of Guayaquil. The joint project of the firms established in the market today as these are exclusively dedicated to the marketing and distribution of ink and toner cartridges or generic imported original and refill system that merely fills the ink cartridges, toners, this is how the market for this kind of cartridges will be recycled is not saturated which is an opportunity for this new product. The focus of this project is to generate economic and environmental benefit for companies of Guayaquil as an ink cartridge recycling through its remanufacturing allows a savings and dramatically reduce the amount of waste generated by an ink cartridge or toner, concrete contributions to the fight against pollution. To determine feasibility of this project were undertaken due to technical market research and administrative, as well as the respective financial evaluation.